2008
DOI: 10.3748/wjg.14.3059
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of the relationship between hepatitis B virus DNA level and risk of hepatocellular carcinoma in Qidong, China

Abstract: AIM:To investigate the role of hepatitis B virus (HBV) replication in the development of hepatocellular carcinoma (HCC), a nested case-control study was performed to study the relationship between HBV DNA level and risk of HCC. METHODS:One hundred and seventy cases of HCC and 276 control subjects free of HCC and cirrhosis were selected for this study. Serum HBV DNA level was measured using fluorescein quantitative polymerase chain reaction at study entry and the last visit. RESULTS:In a binary unconditional lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…The finding of significantly higher HBV viral loads in Black Africans with HCC than in apparently healthy Black carriers of the virus confirms the finding in an earlier study of a small number of Senegalese patients [Tang et al, 2004], and is in keeping with the more extensive results in Taiwanese, Chinese and Japanese patients [Harris et al, 2003;Tang et al, 2004;Yu et al, 2005;Chan et al, 2006;Chen et al, 2006;Fung et al, 2007;Liu et al, 2008;Wu et al, 2008;Yuen et al, 2008]. Because HBeAg status was not available in our control group we are unable to address the question of whether the higher prevalence of HBeAg-positivity among the HCC patients in comparison with asymptomatic HBV carriers could fully account for their differential viral loads.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The finding of significantly higher HBV viral loads in Black Africans with HCC than in apparently healthy Black carriers of the virus confirms the finding in an earlier study of a small number of Senegalese patients [Tang et al, 2004], and is in keeping with the more extensive results in Taiwanese, Chinese and Japanese patients [Harris et al, 2003;Tang et al, 2004;Yu et al, 2005;Chan et al, 2006;Chen et al, 2006;Fung et al, 2007;Liu et al, 2008;Wu et al, 2008;Yuen et al, 2008]. Because HBeAg status was not available in our control group we are unable to address the question of whether the higher prevalence of HBeAg-positivity among the HCC patients in comparison with asymptomatic HBV carriers could fully account for their differential viral loads.…”
Section: Discussionsupporting
confidence: 78%
“…Many longterm follow-up studies in Taiwan, China, and Japan have assessed the relationship between viral loads in chronic carriers of HBV and their subsequent chance of HCC development. These studies showed that high viral loads (defined as !1 Â 10 5 viral copies per ml in some studies [Harris et al, 2003;Chen et al, 2006;Fung et al, 2007;Liu et al, 2008] or !1 Â 10 4 viral copies per ml in others [Yang et al, 2002;Tang et al, 2004;Chan et al, 2006;Wu et al, 2008;Yuen et al, 2008]) predict an increased risk for the development of HCC. The effect of viral load on hepatocarcinogenesis is influenced by a number of variables, including male gender [Chen et al, 2006], HBeAg status [Chen et al, 2002], genotype , and possibly age [Tsai et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Many individuals infected with hepatitis B virus (HBV) become chronic carriers and their liver disease may progress to chronic active hepatitis, cirrhosis, and hepatocellular carcinoma [1] . There is substantial evidence www.wjgnet.com to suggest that adaptive immunity has a central role in determining whether HBV infection is followed by recovery or viral persistence [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Repair related PARP1 activity is suppressed to ensure efficient virus replica tion, while PARP1 binding to the ACTTCAAA sequence of the virus genome provides a signal for transcriptional activation of virus genes [105]. This may trigger expression of the oncogenic properties of HBV, especially when virus DNA accumulates to a high level [118][119][120]. PARP1 increases the efficien cies of virus DNA replication and transcription, while PARP1 dependent ADP ribosylation is inhibited and repair activity is consequently decreased in the infected host cell.…”
Section: Parp1 Dependent Regulation Of Transcriptional Activitymentioning
confidence: 97%